Peran Kepolisian dalam Penanggulangan Balap Liar: Analisis Perspektif Hukum Pidana Islam pada Satlantas Polres Bungo, Jambi - Muhammad Ridho Saputra; Ruslan Abdul Gani; Rahmi Hidayati; Abdul Halim (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Illegal street racing is a persistent issue in Indonesia, including Bungo Regency, endangering road users and violating traffic laws. This study, based on a case study at the Traffic Unit of Bungo Police Resort, aims to explore the police's role in addressing illegal street racing from an Islamic criminal law perspective. Using a qualitative juridical-empirical approach, the study examines legal regulations, institutional practices, and Islamic jurisprudence. Data was gathered from legal sources and literature related to law enforcement and Islamic criminal law. The results reveal that the police play a strategic role in combating street racing through preventative, preemptive, and repressive tactics. Repressive measures include law enforcement based on the Indonesian Traffic and Road Transportation Law, while preventive actions involve community outreach, traffic education, and regular patrols. From an Islamic criminal law viewpoint, illegal street racing is categorized as jarimah ta‘zīr, where authorities impose sanctions to maintain public order and prevent harm (mafsadah), aligning with the maqasid al-shariah goals of preserving property and life. The study concludes that effective and sustainable action against street racing requires collaboration between law enforcement, communities, and religious perspectives.